Analytical sub-domain model for predicting open-circuit field of permanent magnet vernier machine accounting for tooth tips. Issue 2 (7th March 2016) - Oner, Y.; Zhu, Z.Q.; Wu, L.J.; Ge, X.
Abstract : Purpose: – Due to high electromagnetic torque at low speed, vernier machines are suitable for direct-drive applications such as electric vehicles and wind power generators. The purpose of this paper is to present an exact sub-domain model for analytically predicting the open-circuit magnetic field of permanent magnet vernier machine (PMVM) including tooth tips. The entire field domain is divided into five regions, viz. magnets, air gap, slot openings, slots, and flux-modulation pole slots (FMPs). The model accounts for the influence of interaction between PMs, FMPs and slots, and radial/parallel magnetization. Design/methodology/approach: – Magnetic field distributions for slot and air-gap, flux linkage, back-EMF and cogging torque waveforms are obtained from the analytical method and validated by finite element analysis (FEA). Findings: – It is found that the developed sub-domain model including tooth tips is very accurate and is applicable to PMVM having any combination of slots/FMPs/PMs. Originality/value: – The main contributions include: accurate sub-domain model for PMVM is proposed for open-circuit including tooth-tip which cannot be accounted for in literature; the model accounts the interaction between flux modulation pole (FMP) and slot; developed sub-domain model is accurate and applicable to any slot/FMP/PM combinations; and it has investigated the influence of FMP/slot opening width/height on cogging torque.